P-010 Sperm selection by birefringence: a promising non-invasive tool to improve ICSI outcomes. (30th June 2022) - Ribeiro, M; Gomes Da Broi, M; Matos, A; Scaranari, C; Buttros, D; Bragheto, A.M; Faúndes, D
Abstract: Study question: Could the sperm selection by birefringence improve ICSI outcomes in couples with different infertility factors? Summary answer: Sperm selection by birefringence demonstrated a positive clinical impact on ICSI outcomes in couples with different infertility factors when compared to the conventional sperm selection. What is known already: Higher sperm DNA fragmentation may affect ICSI outcomes. However, the utilized sperm selection protocols do not allow the evaluation of this parameter. In this sense, the analysis of sperm's head birefringence has been suggested as an adjuvant of seminal processing in order to select viable sperm for couples with severe male factor. Nevertheless, considering men with normal seminal parameters may also curse with DNA fragmentation, the impact of birefringence on ICSI outcomes of couples with different infertility factors should be investigated. Study design, size, duration: Retrospective case-control study. One hundred eighty-one couples who underwent ICSI from January 2018 to August 2020 [107 submitted to sperm selection by conventional analysis (Nonbirefringence group) and 74 whose sperm were selected by conventional analysis associated to sperm head birefringence evaluation (Birefringence group)] were included in the study. Participants/materials, setting, methods: Medical records were assessed for eligibility evaluation and data collection. Clinical characteristics (female age, body mass index, infertility factor, seminal parameters) and ICSI outcomes (eg. fertilization rate, cleavage rate, blastulation rate, number of high quality embryos formed, implantation rate, biochemical pregnancy rate, clinical pregnancy rate per transfer and per initiated cycle) were compared between the groups using (p < 0.05). A multivariate logistic regression model was applied to verify the factors associated with clinical pregnancy. Main results and the role of chance: Despite the Birefringence group showed higher female age (p = 0.01), lower seminal sperm concentration (p < 0.01) and higher sperm DNA fragmentation (p < 0.01), those patients cursed with higher cleavage rate (p = 0.04), higher clinical pregnancy rate per transfer (p = 0.03) and higher clinical pregnancy rate per initiated cycle (p = 0.02) than the Nonbirefringence group. The logistic regression showed a positive group (Birefrincence) effect on clinical pregnancy achievement. Limitations, reasons for caution: The unequal inclusion of infertility factors between the groups might represent a bias. In logistic regression analysis, none of those factors interfered with clinical pregnancy, which reinforces the impact of the technique on the results. The endpoint analyzed was clinical pregnancy, while live birth would better reflect ICSI success. Wider implications of the findings: Sperm selection by birefringence could positively impact ICSI outcomes. Because it is a cheap and easily reproducible technique, it could be combined with conventional ICSI treatments to improve the reproductive chances of those patients. Trial registration number: not applicable